New Evidence on Development and Cultural Trade: Diversification, Reconcentration and Domination - Maria Masood (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
International trade of cultural goods has considerably increased over the last decades and has been dominated by rich countries's exports. Meanwhile, trade in cultural goods is considered as a potential threat to cultural diversity, and development process is sometimes interpreted as a westernization process. One question arises: how does economic development impact on the cultural diversity of developing countries?This paper investigates the relationship between per capita income and the geographical diversity of cultural imports. Building on the recent literature about cultural diversity, a multi-dimensional approach is applied, taking into account the variety and the balance of cinema and music imports. The results evidence a nonlinear impact of development on the diversity of cultural imports. First, an increase in income leads to a diversification of the varieties consumed. Second, there exists a nonlinear relationship that translates into a reconcentration on a smaller number of partners in latter stage. Third, the reconcentration pattern appears to favour the share of American productsin total cultural imports.
Keywords: O11; F19; Z10; 330